2013
DOI: 10.1111/tid.12071
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive treatment with voriconazole in lung transplant recipients

Abstract: Voriconazole preemptive treatment resulted in low incidence of IFI and IFI-related mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 47 publications
1
28
1
1
Order By: Relevance
“…8 It is noted that retrospective cohort studies have supported the use of voriconazole [9][10][11] ; however, no head-to-head trials have been published comparing the efficacy of azole antifungals in this setting. 8 It is noted that retrospective cohort studies have supported the use of voriconazole [9][10][11] ; however, no head-to-head trials have been published comparing the efficacy of azole antifungals in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…8 It is noted that retrospective cohort studies have supported the use of voriconazole [9][10][11] ; however, no head-to-head trials have been published comparing the efficacy of azole antifungals in this setting. 8 It is noted that retrospective cohort studies have supported the use of voriconazole [9][10][11] ; however, no head-to-head trials have been published comparing the efficacy of azole antifungals in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…4 Several studies have shown a decreased incidence of fungal infections with antifungal prophylaxis. 57 A worldwide survey analyzing the current antifungal prophylactic strategies showed that most transplant centers already use prophylactic antimycotic drugs, with azoles being the preferred agents. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Most are retrospective 7,20,22,32-45 and noncomparative. 22,33,34,36,38,39,[42][43][44][45][46][47][48] Of comparative trials, 7,20,[31][32][33]35,37,40,41,45,49,50 all used a nonrandomized, sequential design, with the exception of Drew et al 51 Although the majority of studies evaluated inhaled formulations of amphotericin B alone, 7,22,31,35,47,51 in combination with, 20,40,43 or as compared with other antifungals, 22,36,37,40,51 universal or targeted 20,50 prophylaxis with oral administration of fluconazole, 20,36,40,49 itraconazole, 20,33,34,…”
Section: Efficacy Of Antifungal Prophylaxis Regimensmentioning
confidence: 99%
“…Key published studies evaluating the efficacy of antifungal prophylaxis in lung transplant recipients are summarized in Table 2. 7,15,20,22,31,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]51 Although inhaled formulations of amphotericin B remain the most widely studied agent for antifungal prophylaxis, their optimal dosages, formulations, and durations of therapy remain unknown. [52][53][54] In pharmacokinetic studies performed in lung transplant recipients, inhaled deoxycholate amphotericin B achieves high concentrations in the lower airways of transplanted lungs, but concentrations at the bronchial anastomosis and in native lungs (in the case of single-lung transplant) are lower.…”
Section: Efficacy Of Antifungal Prophylaxis Regimensmentioning
confidence: 99%
See 1 more Smart Citation